2009
DOI: 10.1007/s00404-009-1199-5
|View full text |Cite
|
Sign up to set email alerts
|

Do women seeking care from obstetrician–gynaecologists prefer to see a female or a male doctor?

Abstract: Purpose To examine whether women seeking care from obstetrician-gynaecologists prefer to see a female or a male doctor or have no preference. Methods Five hundred consecutive women attending gynaecology and antenatal clinics were asked to complete a survey questionnaire containing 12 items requiring opinion on whether they want to be seen by a female or male obstetrician-gynaecologist or have no preference. It also contained questions regarding their reasons for the stated preference. Results Of the consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 16 publications
(14 reference statements)
5
19
1
Order By: Relevance
“…The responses to the current questionnaire survey on 100 lesbians and 100 heterosexual women demonstrated both gender‐based and specific character‐based preferences of Israeli lesbian women. The finding that lesbians significantly prefer female obstetricians/gynecologists compared to heterosexuals is basically similar to other publications that found gender preference for female obstetricians/gynecologists . However, in the present study only 56% of the lesbians preferred female obstetricians/gynecologists while other populations, including Muslims and other Israeli minority groups, such as Arabs and ultra‐orthodox Jewish women, exhibited much higher percentages (>70%).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The responses to the current questionnaire survey on 100 lesbians and 100 heterosexual women demonstrated both gender‐based and specific character‐based preferences of Israeli lesbian women. The finding that lesbians significantly prefer female obstetricians/gynecologists compared to heterosexuals is basically similar to other publications that found gender preference for female obstetricians/gynecologists . However, in the present study only 56% of the lesbians preferred female obstetricians/gynecologists while other populations, including Muslims and other Israeli minority groups, such as Arabs and ultra‐orthodox Jewish women, exhibited much higher percentages (>70%).…”
Section: Discussionsupporting
confidence: 89%
“…The finding that lesbians significantly prefer female obstetricians/gynecologists compared to heterosexuals is basically similar to other publications that found gender preference for female obstetricians/ gynecologists. 38,39,42,43,47,48,50 However, in the present study only 56% of the lesbians preferred female 38,39 exhibited much higher percentages (>70%). Interestingly, we found an unexpected similarity between the lesbian and heterosexual responders; in both populations, more of them showed a preference for a female obstetrician/gynecologist versus a gender preference for a family physician.…”
Section: Discussioncontrasting
confidence: 63%
“…Another possibility to consider are gender biases that patients have for their providers. Although many survey studies conducted in OB/GYN clinics show a majority of women do not have a preference of provider gender, of the remaining patients, only 2–8% favored a male provider, whereas 30% favored a female provider. Perhaps accordingly, there has been a large shift in the gynecology community toward training female providers—a shift that has not occurred quite as significantly among urologists (90% American Urological Association members being male in March 2015).…”
Section: Discussionmentioning
confidence: 93%
“…1 Individual studies have reported various rates for the patients' Ob-Gyn gender preferences, as well as for the factors or motives underlying the patients'responses. [2][3][4] Moreover, gender restriction also occurs regarding student participation in Gynecology consultations, as other articles have mentioned. The bias regarding the involvement of the medical students seems multifaceted and could affect the students' perceptions of the specialty.…”
mentioning
confidence: 99%